2019
DOI: 10.1073/pnas.1914183116
|View full text |Cite
|
Sign up to set email alerts
|

Retroviruses drive the rapid evolution of mammalianAPOBEC3genes

Abstract: APOBEC3(A3) genes are members of theAID/APOBECgene family that are found exclusively in mammals.A3genes encode antiviral proteins that restrict the replication of retroviruses by inducing G-to-A mutations in their genomes and have undergone extensive amplification and diversification during mammalian evolution. Endogenous retroviruses (ERVs) are sequences derived from ancient retroviruses that are widespread mammalian genomes. In this study we characterize theA3repertoire and use the ERV fossil record to explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 79 publications
5
92
0
3
Order By: Relevance
“…Recent work corroborates the presence of A3 retrocopies in some genomes and suggests that the A3 content of mammalian genomes may be even more variable and dynamic than previously appreciated (Hayward et al, 2018;Ito et al, 2020). Our data suggests that A3 retrocopying is more prevalent in NWM genomes compared even to other simian primates.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Recent work corroborates the presence of A3 retrocopies in some genomes and suggests that the A3 content of mammalian genomes may be even more variable and dynamic than previously appreciated (Hayward et al, 2018;Ito et al, 2020). Our data suggests that A3 retrocopying is more prevalent in NWM genomes compared even to other simian primates.…”
Section: Discussionsupporting
confidence: 85%
“…Here, we investigated whether retrocopying may have similarly diversified another family of host defense genes: the APOBEC3 (A3) cytidine deaminases. Although the common ancestor of mammals likely encoded three A3 genes (Münk et al, 2012), this locus has recurrently expanded and contracted throughout mammalian evolution (Ito et al, 2020), including a dramatic expansion to seven paralogous genes in catarrhine primates (Old World monkeys and hominoids) followed by recurrent positive selection of this expanded gene set (Bulliard et al, 2009;Compton et al, 2012;Duggal et al, 2011;Henry et al, 2012;McLaughlin et al, 2016;OhAinle et al, 2006). We found that ancient and ongoing retrocopying has further diversified the already expansive A3 gene locus in primates.…”
Section: Introductionmentioning
confidence: 79%
“…Dynamic evolution of immune-related genes has played an important role in animal evolution 62,[81][82][83] , helping animals adapt to diverse pathogens. The expansion of IR-IFITM genes may reflect an evolutionary response to pathogen pressure in phyllostomid bats.…”
Section: Gene Family Expansion and Contraction Analysismentioning
confidence: 99%
“…The human APOBEC family has nine active family members: APOBEC1, AID, and APOBEC3A/B/C/D/F/G/H [reviewed by (Green & Weitzman, 2019;Harris & Dudley, 2015;Ito, Gifford, & Sato, 2020;Olson, Harris, & Harki, 2018;Silvas & Schiffer, 2019;Simon, Bloch, & Landau, 2015;Siriwardena, Chen, & Bhagwat, 2016)]. Although several APOBEC3s have been implicated in cancer mutagenesis including APOBEC3A (A3A) and APOBEC3H (A3H) (Chan et al, 2015;Nik-Zainal et al, 2014;Starrett et al, 2016;Taylor et al, 2013), a particularly strong case can be made for APOBEC3B (A3B).…”
Section: Introductionmentioning
confidence: 99%